Measuring the performance and excellence of academicians through the e-balanced scorecard (e-BSC) - Hamid, S.; Leen, Y.M.; Pei, S.H. (2008)
Performance measurement and management is always at the heart of any organisations wanting to be seen as transparent, efficient, effective and successful in its operation. Often times, organisations failed in realising their vision and mission as promised to their stakeholders. The most common reason being the failure in executing the strategies or simply the lack of it. University Malaya is currently looking at the balanced scorecard (BSC), introduced by Robert Kaplan and David Norton as a possible answer to this situation. In supporting the university’s effort, this study researches the use of BSC primarily in measuring the performance and excellence of academicians in University Malaya from the perspectives of Internal Business Process (IBP), Learning and Growth (L&G), Financial and Customer. In order to substantiate this research work, a survey and several interviews would be conducted. A framework would be developed as the basis of how the e-BSC for academicians would be built as the outcome of this research.